Old Testament Lessons in the Säʿatat (‘Hours’) of Giyorgis Säglawi - Habtemichael Kidane (Aethiopica, 2019)
This article considers the use of Old Testament readings in the Säʿatat (‘Hours’) of Abba Giyorgis Säglawi (d.1425), an unusual practice in Gǝʿǝz liturgy. It is believed that the introduction of Old Testament readings into the Säʿatat went through various stages. It was first introduced on Saturdays to better understand the greatness of the day on which God rested. It was then extended to Sunday. It seems certain that the question of the Sabbath(s) influenced the introduction of Old Testament readings into the celebration of the Säʿatat. The Old Testament readings in the Säʿatat are protracted because the Scriptures are the Word of God, and therefore there should be no discrimination in their usage. Reading from both the Old and the New Testaments is also connected to the idea that they represent the two breasts of the Church, an image depicted more clearly in Giyorgis than in the gädlat of other local saints. Thus, the children of the Church must be fed readings from both Testaments which are the breasts of their mother, the Church. Today, one finds readings from the Old Testament at almost every hour of the Säʿatat. However, readings from both Testaments did not extend beyond the Säʿatat, neither into the Liturgy of the Qǝddase (Eucharistic celebration), nor the Yaredian/Dǝggwa Divine Office.